Oxidative Difluoromethylation of Tetrahydroisoquinolines Using TMSCF2SPh: Synthesis of Fluorinated Pyrrolo[2,1-a]isoquinolines and Benzo[a]quinolizidines - Teerachai Punirun (2019)
© 2017 American Chemical Society. An efficient C1-difluoromethylation of tetrahydroisoquinolenes was achieved using TMSCF2SPh as a difluoromethylating agent and 2,2,6,6-tetramethylpiperidine-1-oxoammonium tetrafluoroborate (TEMPO+BF4-) as an oxidant. The process provides an access to a variety of C1-difluoro(phenylsulfanyl)methylated tetrahydroisoquinoline adducts in good yields. These adducts were employed as key precursors for preparing fluorinated pyrrolo[2,1-a]isoquinoline and benzo[a]quinolizidines.